TIPE PENGUNJUNG AIR TERJUN TUJUH TINGKAT DI DESA LUBUK AMBACANG KECAMATAN HULU KUANTAN KABUPATEN KUANTAN SINGINGI - Fitriani, Willy; Sulistyani, Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study aims to determine (1) to determine the type of tourist visiting Niagara Seven Levels in the village of Lubuk Ambacang District of Hulu Kuantan Kuantan District Singingi; (2) the development efforts in accordance with the type of visitor facilities Waterfall Seven Levels in the village of Lubuk Ambacang District of Hulu Kuantan Kuantan District Singingi. This study used a qualitative method with descriptive approach, the subject of this research is the key informen namely, Guest Niagara Level Seven, Community Neighborhood Attractions. The data collection is made by, observation, interview, documentation and document research. Analysis of the data used in this study, namely, information collection, data reduction, data presentation, and conclusion.The results showed that (1) the visitors who come to the attractions Niagara Level Seven is the type of visitor Mass Tourism (mass tourism) it is characterized by some of the characteristics or nature of the visitors who showed mass tourism as visitors come in groups of more than five people, visit tourist destination, just to relax, enjoy the scenery and enjoy the waterfalls, prefer to plan their travel alone, travel independently, are more spontaneous and flexible in organizing the journey and encouraged them to seek attraction with a special interest such as ecotourism and adventure travel; (2) the type of visitors who come to Niagara Seven Levels and visitors need for development or facilities development effort required in accordance with the type of visitor and tourism activities are carried out.Keywords: Waterfall Tujuh Tingkat, Visitor Type